Engenering laboratory in educational institutions - Терехов, Андрей Николаевич; Геворкян, Татьяна Георгиевна; Киселев, Михаил Михайлович; Немешев, Марат Халимович (Computer Tools in Education, 2015)
The main attention in this article is paid to the development of engineering education in our country, particularly in educational institutions. Modern students often do not know how to use the wrench and screwdriver, do not know the unit outlet or electrical switch. In the schools there is a subject "Technology where use of project-based approach in the classroom is prescribed (focus on industrial labor and management at home), but there are no detailed guidelines. This article describes the authors’ experience in the use of robotics construction set TRIK and graphics technology TRIK Studio in additional education and in the "Technology"classes in the Saint Petersburg lyceum № 419. We came to the conclusion that robots can serve as a good bridge to the general engineering education, and covering the whole cycle of learning from students in elementary school to university students, and industrial use. The development of tools for such an ambitious aim is a complicated scientific and technical task. The authors propose a project of the engineering laboratories, which would be a kind of resource center of educational institution.
Keywords: school subject; robotics; engineering education; graphical programming techniques; methods of education